How does Implementation Drive Actual Buying Behavior of Organic Coffee? - Tinneke Hermina; Hanifah Fauziah (Publindo Akademika, 2022)
Environmental issues have become a global problem, making people more aware of environmentally friendly aspects of their daily lives. MSME coffee in Garut Regency is one of the subjects contributing to protecting environmental sustainability by promoting green marketing. However, the Indonesian people's views toward green products considered expensive are many factors that consumers choose non-green products. It means there is a gap between attitudes and behavior, which shows that consumers' positive attitudes towards products are not necessarily actualized in buying. The current research is aimed at analyzing the influence of the condition of the consumer's social environment on actual buying behavior through the implementation of coffee products among millennials in the Garut Regency. The results showed that the condition of the consumer's social environment influences actual buying behavior through implementation intention on coffee products among millennials in Garut Regency directly and indirectly.